Selection of Optimum Structural Schemes of Rod Spatial Structures - Isabekov, K.; Gulomov, N.G. (European Journal of Life Safety and Stability (2660-9630), 2022)
The article gives recommendations on the design of optimal earthquake-resistant cross-rod spatial structures, taking into account the peculiarities of the influence of the location of supports and their number in relation to the frames of one-story industrial and civil buildings